Tradisi Bersedekah Dengan Bacaan Al-Qur’an Untuk Orang Meninggal: Analisis Komparatif Penafsiran Al-Qurṭubī dan Sayyid Quṭb - Eka Cahya (Kartika: Jurnal Studi Keislaman, 2026)
The practice of dedicating the spiritual rewards of good deeds to the deceased represents a religious issue at the intersection of individual accountability and the doctrine that certain deeds may benefit others. Divergent understandings of this relationship have generated a range of views among Qur’anic exegetes and Islamic jurists. This study aims to comparatively analyze the interpretations of al-Qurṭubī in Al-Jāmi‘ li Aḥkām al-Qur’ān and Sayyid Quṭb in Fī Ẓilāl al-Qur’ān concerning Qur’an 2:286, 36:54, and 53:39, and to examine their implications for the question of dedicating spiritual rewards to the deceased. This study employs library research using the comparative (muqāran) method of Qur’anic interpretation and content analysis. The findings indicate that both exegetes affirm the principle of human responsibility for individual deeds and the justice of God in determining their recompense. However, al-Qurṭubī interprets this principle by integrating Qur’anic verses with Prophetic traditions and juristic opinions, thereby allowing room for the possibility that certain deeds performed by others may benefit the deceased when supported by valid scriptural evidence. By contrast, Sayyid Quṭb emphasizes the moral and theological dimensions of the verses, particularly individual agency, personal responsibility, and the cultivation of religious consciousness, without making the transmission of spiritual rewards to the deceased a primary concern of his interpretation. These differences demonstrate that exegetical orientation and methodological approach influence how Qur’anic principles are related to juridical issues emerging within Muslim society.